The imperative of palliation in the management of rabies encephalomyelitis - Warrell, M; Warrell, D; Tarantola, A (MDPI, 2017)
The aim of this review is to guide clinicians in the practical management of patients suffering from rabies encephalomyelitis. This condition is eminently preventable by modern post-exposure vaccination, but is virtually always fatal in unvaccinated people. In the absence of any proven effective antiviral or other treatment, palliative care is an imperative to minimise suffering. Suspicion of rabies encephalomyelitis depends on recognising the classic symptomatology and eliciting a history of exposure to a possibly rabid mammal. Potentially treatable differential diagnoses must be eliminated, notably other infective encephalopathies. Laboratory confirmation of suspected rabies is not usually possible in many endemic areas, but is essential for public health surveillance. In a disease as agonising and terrifying as rabies encephalomyelitis, alleviation of distressing symptoms is the primary concern and overriding responsibility of medical staff. Calm, quiet conditions should be created, allowing relatives to communicate with the dying patient in safety and privacy. Palliative management must address thirst and dehydration, fever, anxiety, fear, restlessness, agitation, seizures, hypersecretion, and pain. As the infection progresses, coma and respiratory, cardiovascular, neurological, endocrine, or gastrointestinal complications will eventually ensue. When the facilities exist, the possibility of intensive care may arise, but although some patients may survive, they will be left with severe neurological sequelae. Recovery from rabies is extremely rare, and heroic measures with intensive care should be considered only in patients who have been previously vaccinated, develop rabies antibody within the first week of illness, or were infected by an American bat rabies virus. However, in most cases, clinicians must have the courage to offer compassionate palliation whenever the diagnosis of rabies encephalomyelitis is inescapable